Method for magnetron sputtering of FeCrAlTi-yttrium oxide coating on surface of austenite 316L steel
By using magnetron sputtering technology to prepare FeCrAlTi-yttrioxide coating on the surface of austenite 316L steel, the corrosion problem of lead-bismuth alloy coolant on structural materials is solved, and the mechanical and corrosion properties of the material are significantly improved. It is suitable for Structural materials of lead-based reactors.
Patent Information
- Application Number
- CN202411582759.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-07
AI Technical Summary
Lead-bismuth alloys, as coolants, have severe erosion on structural materials, resulting in dissolution and oxidative corrosion of structural materials in high-temperature liquid lead-bismuth eutectic environments.
The method of magnetron sputtering FeCrAlTi-yttrioxide coating on the surface of austenite 316L steel was used to coat the film under specific conditions by a direct current magnetron sputtering device to prepare a composite target material with high purity and good controllability.
Effectively improve the mechanical properties and resistance to lead-bismuth eutectic (LBE) corrosion of 316L austenitic steel. The resulting coating thickness can reach 5μm to 7μm, with good film-based binding force and uniform distribution, and can be at the extreme. Provides radiation/corrosion protection in working conditions.
Smart Images

Figure CN119411086A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for magnetron sputtering coating on a steel surface. Background Art
[0002] Energy is an important material basis for human survival and a source of power for the development of human society. Nuclear energy is highly efficient, clean and safe, and is internationally recognized as a new energy source that can be applied on a large scale. In the early 21st century, in order to minimize nuclear waste and improve the nuclear fuel cycle, the fourth generation of reactors was creatively proposed, which included six types of reactors. Lead-based reactors are an advanced nuclear energy system. Lead-based reactors include: lead-cooled fast reactor system (LFR) and accelerator-driven subcritical system (ADS). Lead-cooled fast reactors are considered to be one of the most promising nuclear reactors in the future.
[0003] The lead-cooled fast reactor in the fourth generation nuclear energy system is named because its coolant is pure lead or lead-bismuth alloy. It has the following advantages: (1) high safety performance; (2) sustainable supply of nuclear fuel; (3) good economic effect. Stainless steel structural materials are often used as structural materials for LFR and ADS because of their good high-temperature oxidation resistance, neutron irradiation resistance, good thermal conductivity and cold processing properties. At present, the main choice for the main container of lead-based fast reactors in the world is 316L austenitic stainless steel. However, using lead-bismuth alloy as coolant also has some disadvantages for structural materials, such as serious corrosion to structural materials: in the high-temperature liquid lead-bismuth eutectic (LBE) environment, structural materials are very susceptible to dissolution corrosion and oxidation corrosion. As the corrosion temperature and the dissolved oxygen concentration in the liquid lead-bismuth alloy change, these two corrosion behaviors will jointly affect the corrosion resistance of the material. Summary of the invention
[0004] The present invention aims to solve the problem that the existing lead-bismuth alloy used as a coolant has serious corrosion on structural materials, and further provides a method for magnetron sputtering FeCrAlTi-yttrium oxide coating on the surface of austenitic 316L steel.
[0005] A method for magnetron sputtering FeCrAlTi-yttrium oxide coating on the surface of austenitic 316L steel is carried out according to the following steps:
[0006] 1. Target installation and sputtering pretreatment:
[0007] The 53Fe18Cr13Al8Ti-8Y2O3 composite target was installed on the target position of the DC magnetron sputtering device, the austenitic 316L steel substrate was placed on the sample stage of the DC magnetron sputtering device, the distance between the sample and the target head was adjusted, the chamber door was closed, the vacuum was evacuated and argon gas was introduced, the negative bias voltage power supply was turned on, and then the austenitic 316L steel substrate was pre-sputtered;
[0008] 2. Magnetron sputtering:
[0009] After pre-sputtering, the rotation speed of the sample stage is adjusted, and magnetron sputtering coating is performed under the conditions of a working pressure of 0.4Pa-0.7Pa in the chamber, a temperature of 60℃-150℃ in the chamber, a current of 0.2A-0.4A and a negative bias voltage of 0V-200V. The chamber vacuum is then maintained and cooled to room temperature. Finally, the sample is taken out to complete the method of magnetron sputtering FeCrAlTi-yttrium oxide coating on the surface of austenitic 316L steel.
[0010] The beneficial effects of the present invention are:
[0011] 1. The present invention prepares a composite target material by a powder metallurgy method, wherein Y2O3 nano-oxide can be dispersed into a FeCrAlTi alloy, wherein the target material purity is ≥99.9%, and the target material can be reused many times, which can effectively overcome the complex process conditions such as double-target sputtering required for traditional Y2O3, and can use DC magnetron sputtering for the preparation of coating materials, and its sputtering rate is faster than that of RF magnetron sputtering.
[0012] 2. The present invention introduces dispersed nanoparticles of Y2O3. The small and dispersed Y2O3 particles are the key to improving its mechanical properties and LBE corrosion resistance. The process of the present invention has strong controllability and is easy to implement. It can be used on the surface of lead-based fast reactor structural materials. The thickness of the prepared coating can reach 5μm to 7μm, which can improve the mechanical properties and lead-bismuth eutectic (LBE) corrosion resistance of 316L austenitic steel to a certain extent, and can be applied to radiation / corrosion-resistant coating materials for lead-based reactor structural materials under extreme working conditions. The prepared coating membrane has no bad pores, good bonding strength, and the coating is evenly distributed without obvious defects.
[0013] Instruction Manual
[0014] Figure 1 Schematic diagrams of SEM and EDS of the cross section of the coating in austenitic 316L steel with the surface magnetron sputtering FeCrAlTi-Y2O3 coating prepared in Example 1, (a) is a SEM image with a scale of 100 μm, (b) is a SEM image with a scale of 10 μm, (c) is a SEM image with a scale of 5 μm, and (d) is an EDS image;
[0015] Figure 2 The GIXRD spectrum of the coating in austenitic 316L steel with the surface magnetron sputtering FeCrAlTi-Y2O3 coating prepared in Example 1;
[0016] Figure 3Schematic diagrams of SEM and EDS of the cross section of the coating in austenitic 316L steel with the surface magnetron sputtering FeCrAlTi-Y2O3 coating prepared in Example 2, (a) is a SEM image with a scale of 100 μm, (b) is a SEM image with a scale of 10 μm, (c) is a SEM image with a scale of 5 μm, and (d) is an EDS image;
[0017] Figure 4 The GIXRD spectrum of the coating in austenitic 316L steel with the surface magnetron sputtering FeCrAlTi-Y2O3 coating prepared in Example 2;
[0018] Figure 5 Schematic diagrams of SEM and EDS of the cross section of the coating in austenitic 316L steel with the surface magnetron sputtering FeCrAlTi-Y2O3 coating prepared in Example 3, (a) is a SEM image with a scale of 100 μm, (b) is a SEM image with a scale of 10 μm, (c) is a SEM image with a scale of 5 μm, and (d) is an EDS image;
[0019] Figure 6 The GIXRD spectrum of the coating in austenitic 316L steel with the surface magnetron sputtering FeCrAlTi-Y2O3 coating prepared in Example 3;
[0020] Figure 7 The XPS spectrum of the coating in austenitic 316L steel with the surface magnetron sputtering FeCrAlTi-Y2O3 coating prepared in Example 2;
[0021] Figure 8 Schematic diagram of nanoindentation of the coating and substrate in austenitic 316L steel with surface magnetron sputtering FeCrAlTi-Y2O3 coating prepared in Examples 1 to 3, (a) is the nanoindentation displacement-load curve, and (b) is the indentation hardness H and the reduced elastic modulus E;
[0022] Fig. 9 The SEM images of the coating on austenitic 316L steel with the surface magnetron sputtered FeCrAlTi-Y2O3 coating prepared in Example 1 after being subjected to LBE corrosion at 550°C for 100h, (a) has a scale of 10μm, (b) has a scale of 5μm;
[0023] Fig.10 Schematic diagram of the cross-section SEM and EDS of the coating on austenitic 316L steel with a surface magnetron sputtered FeCrAlTi-Y2O3 coating prepared in Example 2 after irradiation with a total dose of 1 MGy of γ-rays and then subjected to 650°C LBE corrosion for 500 h, (a) is the SEM image, and (b) is the EDS image. DETAILED DESCRIPTION
[0024] Specific implementation method 1: This implementation method is a method for magnetron sputtering FeCrAlTi-yttrium oxide coating on the surface of austenitic 316L steel, which is carried out according to the following steps:
[0025] 1. Target installation and sputtering pretreatment:
[0026] The 53Fe18Cr13Al8Ti-8Y2O3 composite target was installed on the target position of the DC magnetron sputtering device, the austenitic 316L steel substrate was placed on the sample stage of the DC magnetron sputtering device, the distance between the sample and the target head was adjusted, the chamber door was closed, the vacuum was evacuated and argon gas was introduced, the negative bias voltage power supply was turned on, and then the austenitic 316L steel substrate was pre-sputtered;
[0027] 2. Magnetron sputtering:
[0028] After pre-sputtering, the rotation speed of the sample stage is adjusted, and magnetron sputtering coating is performed under the conditions of a working pressure of 0.4Pa-0.7Pa in the chamber, a temperature of 60℃-150℃ in the chamber, a current of 0.2A-0.4A and a negative bias voltage of 0V-200V. The chamber vacuum is then maintained and cooled to room temperature. Finally, the sample is taken out to complete the method of magnetron sputtering FeCrAlTi-yttrium oxide coating on the surface of austenitic 316L steel.
[0029] In this specific implementation method, after the coating is prepared, the target baffle, heating device, DC power supply, and sample stage rotation are turned off in sequence, and the vacuum is maintained until the chamber is slowly cooled to room temperature. This cooling method can effectively reduce the internal stress generated by the coating during the cooling process, and then the sample is taken out and placed in a membrane box.
[0030] The beneficial effects of this implementation are:
[0031] 1. In this embodiment, a composite target material is prepared by a powder metallurgy method, wherein Y2O3 nano-oxide can be dispersed in a FeCrAlTi alloy, wherein the target material purity is ≥99.9%, and the target material can be reused many times, which can effectively overcome the complex process conditions such as double-target sputtering required for traditional Y2O3, and DC magnetron sputtering can be used for the preparation of coating materials, and its sputtering rate is faster than that of RF magnetron sputtering.
[0032] 2. This embodiment introduces dispersed Y2O3 nanoparticles. The small and dispersed Y2O3 particles are the key to improving its mechanical properties and LBE corrosion resistance. This embodiment has strong process controllability and is easy to implement. It can be used on the surface of lead-based fast reactor structural materials. The thickness of the prepared coating can reach 5μm to 7μm, which can improve the mechanical properties and lead-bismuth eutectic (LBE) corrosion resistance of 316L austenitic steel to a certain extent, and can be used in radiation / corrosion-resistant coating materials for lead-based reactor structural materials under extreme working conditions. The prepared coating membrane has no bad pores, good bonding strength, and the coating is evenly distributed without obvious defects.
[0033] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the 53Fe18Cr13Al8Ti-8Y2O3 composite target described in step 1 is specifically prepared according to the following steps: Fe powder, Cr powder, Al powder, Ti powder and Y2O3 ceramic oxide powder are mixed in an atomic ratio of 53:18:13:8:8 to obtain an alloyed mixed powder, and the alloyed mixed powder is pressurized and sintered for 5min to 10min in an Ar atmosphere at a pressure of 260MPa to 300MPa and a sintering temperature of 900℃ to 1000℃ to obtain a FeCrAlTi-Y2O3 composite target. The rest is the same as specific implementation method 1.
[0034] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the austenitic 316L steel substrate described in step one is obtained after pretreatment; the pretreatment is specifically carried out according to the following steps: the surface of the austenitic 316L steel substrate is polished with 400#, 800#, 1200#, 2000# and 3000# sandpaper in turn, and then polished with polishing liquid with a particle size of 1.5μm, 1.0μm and 0.5μm in turn until there are no obvious scratches on the surface, and then ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 10min to 15min in turn, and finally taken out and dried. The rest is the same as specific implementation method one or two.
[0035] Specific implementation method 4: This implementation method is different from specific implementation methods 1 to 3 in that the distance between the sample and the target head is adjusted to 4 cm to 6 cm in step 1. The rest is the same as specific implementation methods 1 to 3.
[0036] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: in step 1, evacuating and introducing argon gas are specifically carried out in the following steps: vacuumizing to 1.5×10 -3 Pa~1.5×10 -4Pa, then Ar gas is introduced and the Ar gas flow rate is adjusted to make the working gas pressure in the chamber 0.4 Pa to 0.7 Pa. The rest is the same as the first to fourth embodiments.
[0037] Specific implementation example 6: This implementation example is different from specific implementation examples 1 to 5 in that the Ar gas flow rate is adjusted to 90 sccm / min to 120 sccm / min. The rest is the same as specific implementation examples 1 to 5.
[0038] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that the pre-sputtering described in step 1 is performed for 5 to 10 minutes under the conditions of a working pressure of 0.4 Pa to 0.7 Pa in the chamber, a temperature of 60° C. to 150° C. in the chamber, a DC current of 0.2 A to 0.4 A, and a negative bias voltage of 300 V to 500 V. The rest is the same as specific embodiments 1 to 6.
[0039] Specific embodiment 8: This embodiment is different from specific embodiments 1 to 7 in that the thickness of the magnetron sputtering coating in step 2 is 5 μm to 7 μm. The rest is the same as specific embodiments 1 to 7.
[0040] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that the magnetron sputtering coating in step 2 is performed for 2h to 4h. The rest is the same as specific embodiments 1 to 8.
[0041] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the rotation speed of the sample stage is adjusted to 10 r / min to 15 r / min in step 2. The rest is the same as specific embodiments 1 to 9.
[0042] The following examples are used to verify the beneficial effects of the present invention:
[0043] Embodiment 1:
[0044] A method for magnetron sputtering FeCrAlTi-yttrium oxide coating on the surface of austenitic 316L steel is carried out according to the following steps:
[0045] 1. Target installation and sputtering pretreatment:
[0046] The 53Fe18Cr13Al8Ti-8Y2O3 composite target was installed on the target position of the DC magnetron sputtering device, and the austenitic 316L steel substrate was placed on the sample stage of the DC magnetron sputtering device. The distance between the sample and the target head was adjusted to 4 cm. After the chamber door was closed, the vacuum was evacuated and argon gas was introduced. The negative bias voltage power supply was turned on, and then the austenitic 316L steel substrate was pre-sputtered for 10 minutes under the conditions of a working pressure of 0.6 Pa in the chamber, a temperature of 150°C in the chamber, a DC current of 0.3A, and a negative bias voltage of 500V.
[0047] 2. Magnetron sputtering:
[0048] After pre-sputtering, the sample stage speed was adjusted, and magnetron sputtering coating was carried out for 4 hours under the conditions of sample stage speed of 10r / min, working gas pressure in the chamber of 0.6Pa, temperature in the chamber of 150℃, current of 0.3A and negative bias voltage of 0V. Then the chamber vacuum was maintained and cooled to room temperature. Finally, the sample was taken out to obtain austenitic 316L steel with surface magnetron sputtered FeCrAlTi-Y2O3 coating.
[0049] The 53Fe18Cr13Al8Ti-8Y2O3 composite target described in step one is specifically prepared according to the following steps: Fe powder, Cr powder, Al powder, Ti powder and Y2O3 ceramic oxide powder are mixed in an atomic ratio of 53:18:13:8:8 to obtain an alloyed mixed powder; and the alloyed mixed powder is pressurized and sintered for 5 minutes in an Ar atmosphere, a pressure of 300 MPa and a sintering temperature of 1000°C to obtain a FeCrAlTi-Y2O3 composite target; the target purity is ≥99.9%.
[0050] The austenitic 316L steel substrate described in step 1 is obtained after pretreatment; the pretreatment is specifically carried out according to the following steps: the surface of the austenitic 316L steel substrate is polished with 400#, 800#, 1200#, 2000# and 3000# sandpaper in turn, and then polished with polishing liquids with particle sizes of 1.5μm, 1.0μm and 0.5μm in turn until there are no obvious scratches on the surface, and then ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 10 minutes in turn, and finally taken out and dried.
[0051] The vacuuming and introduction of argon in step 1 are specifically carried out in the following steps: vacuuming to 1.5×10 -4 Pa, and then Ar gas was introduced and the Ar gas flow rate was adjusted to 120 sccm / min, so that the working gas pressure in the chamber was 0.6 Pa.
[0052] The thickness of the magnetron sputtering coating in step 2 is 6.88 μm.
[0053] Embodiment 2: This embodiment is different from Embodiment 1 in that: the negative bias voltage in step 2 is 100V; the thickness of the magnetron sputtering coating in step 2 is 6.70 μm. The rest is the same as Embodiment 1.
[0054] Embodiment 3: This embodiment is different from Embodiment 1 in that: the negative bias voltage in step 2 is 200V; the thickness of the magnetron sputtering coating in step 2 is 5.73 μm. The rest is the same as Embodiment 1.
[0055] Figure 1 Schematic diagram of SEM and EDS of the coating cross section in austenitic 316L steel of the surface magnetron sputtering FeCrAlTi-Y2O3 coating prepared in Example 1, (a) is the SEM image with a scale of 100 μm, (b) is the SEM image with a scale of 10 μm, (c) is the SEM image with a scale of 5 μm, and (d) is the EDS image; it can be seen from the figure that the thickness of the prepared FeCrAlTi-Y2O3 coating is about 6.88 μm, there is an obvious interface between the alloy coating and the substrate material, and there are no bad pores on the surface of the alloy coating and the substrate material 316L steel, indicating that there is good film-base bonding between the two. It can be seen from the cross-sectional EDS image that the deposited coating elements are evenly distributed, no obvious element aggregation and segregation are observed, and Ti and Y elements are enriched on the surface of the alloy coating.
[0056] Figure 2 This is the GIXRD spectrum of the coating in austenitic 316L steel with surface magnetron sputtering FeCrAlTi-Y2O3 coating prepared in Example 1; as can be seen from the figure, the prepared FeCrAlTi-Y2O3 coating material exhibits an obvious amorphous structure, with two broad peaks at 2θ=33° and 2θ=45°, the coating has no obvious defects, and no diffraction peaks of the substrate material 316L steel are detected.
[0057] Figure 3 Schematic diagram of SEM and EDS of the coating cross section in austenitic 316L steel of the surface magnetron sputtering FeCrAlTi-Y2O3 coating prepared in Example 2, (a) is the SEM image with a scale of 100 μm, (b) is the SEM image with a scale of 10 μm, (c) is the SEM image with a scale of 5 μm, and (d) is the EDS image; it can be seen from the figure that the thickness of the prepared FeCrAlTi-Y2O3 coating is about 6.70 μm, which also shows that there is an obvious interface between the alloy coating and the substrate material, and there are no bad pores between the alloy coating and the surface of the substrate material austenitic 316L steel, indicating that the two have good film-base bonding.
[0058] Figure 4This is the GIXRD spectrum of the coating in austenitic 316L steel with the surface magnetron sputtering FeCrAlTi-Y2O3 coating prepared in Example 2; as can be seen from the figure, the prepared FeCrAlTi-Y2O3 coating material exhibits an obvious amorphous structure, in which the diffraction peak of the Fe-Cr phase is enhanced.
[0059] Figure 5 Schematic diagram of SEM and EDS of the coating cross section in austenitic 316L steel of the surface magnetron sputtering FeCrAlTi-Y2O3 coating prepared in Example 3, (a) is the SEM image with a scale of 100 μm, (b) is the SEM image with a scale of 10 μm, (c) is the SEM image with a scale of 5 μm, and (d) is the EDS image; it can be seen from the figure that the thickness of the prepared FeCrAlTi-Y2O3 coating is about 5.73 μm, and there is an obvious interface between the coating and the substrate. The EDS image shows that the coating is successfully prepared, the coating elements are evenly distributed, no obvious element aggregation and segregation are observed, and the Ti and Y elements are enriched on the surface of the alloy coating.
[0060] By comparison, it was found that the coating thickness decreased with the increase of the applied bias voltage, indicating that the coating deposition rate decreased to a certain extent with the increase of the bias voltage. The increase of the bias voltage reduced the atomic deposition rate on the coating surface. The larger ion flux promoted the migration and filling of the deposited atoms on the substrate surface and improved the density of the coating surface, resulting in the coating deposition rate decreasing with the increase of the bias voltage.
[0061] Figure 6 This is the GIXRD spectrum of the coating in austenitic 316L steel with the surface magnetron sputtering FeCrAlTi-Y2O3 coating prepared in Example 3. As can be seen from the figure, the coating exhibits an amorphous structure, and the coating with an amorphous structure is beneficial to improving the oxidation resistance of the material.
[0062] Figure 7 XPS spectrum of the coating in austenitic 316L steel prepared in Example 2 by magnetron sputtering of FeCrAlTi-Y2O3 coating. As can be seen from the figure, 157.5eV and 159.5eV correspond to Y 3d 5 / 2 and Y 3d 3 / 2 The electron binding energy of the FeCrAlTi-Y2O3 alloy coating shows that the Y element exists in the alloy coating in various forms such as Y2O3. No metal Y3d peak is found at 155.6eV, indicating that the content of metal Y in the film is small or non-existent. XPS data show that the successful preparation of the FeCrAlTi-Y2O3 alloy coating and the successful incorporation of Y2O3 dispersed metal oxide play a vital role in improving the coating material's resistance to high-temperature oxidation and radiation corrosion.
[0063] Figure 8Schematic diagram of nanoindentation of coating and substrate in austenitic 316L steel with surface magnetron sputtering FeCrAlTi-Y2O3 coating prepared in Examples 1 to 3, (a) is the nanoindentation displacement-load curve, (b) is the indentation hardness H and the reduced elastic modulus E; the maximum load is set to 20mN; it can be seen from the figure that: the nanohardness of the coating in Example 3 can reach up to 11.52Gpa, the nanohardness of the base material 316L steel is only 5.49Gpa, the coating improves its nanohardness by more than double, under the same maximum load pressure, the indentation depth of the 316L steel substrate is about 450nm, and the indentation depth of the sample prepared in Example 3 is only 300nm.
[0064] Fig. 9 This is an SEM image of the coating in austenitic 316L steel with a surface magnetron sputtered FeCrAlTi-Y2O3 coating prepared in Example 1 after being corroded by LBE at 550°C for 100h, (a) is a scale of 10μm, (b) is a scale of 5μm; the Pb content in the LBE is 44.5at.%, and the Bi content is 55.5at.%; as can be seen from the figure, a large amount of oxides are generated on the surface of the alloy coating in Example 1 after LBE corrosion, and the generated oxides can effectively inhibit the further penetration of LBE, and there is 1.38at.% Pb on the surface, and the contents of Ti and Y elements are 2.21at.% and 4.72at.%, respectively.
[0065] After 100 h of LBE corrosion at 550°C, only 0.16 at.% Bi was present on the surface of Example 2, and the contents of Ti and Y were 2.18 at.% and 4.69 at.%, respectively. After 100 h of LBE corrosion at 550°C, a certain amount of lead-bismuth alloy remained on the surface of Example 3, in which 0.5 at.% Pb and 0.16 at.% Bi were present, and the contents of Ti and Y were 1.74 at.% and 4.28 at.%, respectively, indicating that a certain amount of Pb oxide was generated. However, the coatings prepared in Examples 1 to 3 were still intact after 100 h of LBE corrosion at 550°C. The preparation of a dense FeCrAlTi-Y2O3 alloy coating under certain conditions can improve the corrosion resistance of the substrate.
[0066] Fig.10The cross-sectional SEM and EDS diagrams of the coating on austenitic 316L steel with a surface magnetron sputtered FeCrAlTi-Y2O3 coating prepared in Example 2 after irradiation with a total dose of 1MGy of γ-rays and then subjected to 650°C LBE corrosion for 500h, (a) is the SEM diagram, and (b) is the EDS diagram; the Pb content in the LBE is 44.5at.%, and the Bi content is 55.5at.%; it can be seen from the figure that the entire oxide layer can be divided into an outer oxide layer and an inner oxide layer, wherein the outer oxide layer is mainly a composite oxide of Fe, and the thickness of the outer oxide layer is about 15μm, and the inner oxide layer is mainly a composite oxide of Cr, and the thickness of the inner oxide layer is about 20μm, wherein the LBE alloy is confined to the surface of the coating, and the FeCrAlTi-Y2O3 coating can effectively inhibit the further penetration of LBE, thereby improving the radiation / corrosion resistance of the substrate in extreme corrosion environments.
Claims
1. A method for magnetron sputtering FeCrAlTi-yttrium oxide coating on the surface of austenitic 316L steel, characterized in that It is carried out in the following steps:
1. Target installation and sputtering pretreatment: The 53Fe18Cr13Al8Ti-8Y2O3 composite target was installed on the target position of the DC magnetron sputtering device, the austenitic 316L steel substrate was placed on the sample stage of the DC magnetron sputtering device, the distance between the sample and the target head was adjusted, the chamber door was closed, the vacuum was evacuated and argon gas was introduced, the negative bias voltage power supply was turned on, and then the austenitic 316L steel substrate was pre-sputtered; 2. Magnetron sputtering: After pre-sputtering, the rotation speed of the sample stage is adjusted, and magnetron sputtering coating is performed under the conditions of a working pressure of 0.4Pa-0.7Pa in the chamber, a temperature of 60℃-150℃ in the chamber, a current of 0.2A-0.4A and a negative bias voltage of 0V-200V. The chamber vacuum is then maintained and cooled to room temperature. Finally, the sample is taken out to complete the method of magnetron sputtering FeCrAlTi-yttrium oxide coating on the surface of austenitic 316L steel.
2. The method for magnetron sputtering FeCrAlTi-yttrium oxide coating on the surface of austenitic 316L steel according to claim 1, characterized in that The 53Fe18Cr13Al8Ti-8Y2O3 composite target described in step one is specifically prepared according to the following steps: Fe powder, Cr powder, Al powder, Ti powder and Y2O3 ceramic oxide powder are mixed in an atomic ratio of 53:18:13:8:8 to obtain an alloyed mixed powder; and the alloyed mixed powder is pressurized and sintered for 5 min to 10 min in an Ar atmosphere, a pressure of 260 MPa to 300 MPa and a sintering temperature of 900°C to 1000°C to obtain a FeCrAlTi-Y2O3 composite target.
3. The method for magnetron sputtering FeCrAlTi-yttrium oxide coating on the surface of austenitic 316L steel according to claim 1, characterized in that The austenitic 316L steel substrate described in step 1 is obtained after pretreatment; the pretreatment is specifically carried out according to the following steps: the surface of the austenitic 316L steel substrate is polished using 400#, 800#, 1200#, 2000# and 3000# sandpaper in turn, and then polished using polishing liquids with particle sizes of 1.5μm, 1.0μm and 0.5μm in turn until there are no obvious scratches on the surface, and then ultrasonically cleaned with acetone, anhydrous ethanol and deionized water for 10min to 15min, and finally taken out and dried.
4. The method for magnetron sputtering FeCrAlTi-yttrium oxide coating on the surface of austenitic 316L steel according to claim 1, characterized in that In step 1, the distance between the sample and the target head is adjusted to 4 cm to 6 cm.
5. The method for magnetron sputtering FeCrAlTi-yttrium oxide coating on the surface of austenitic 316L steel according to claim 1, characterized in that The vacuuming and introduction of argon in step 1 are specifically carried out in the following steps: vacuuming to 1.5×10 -3 Pa~1.5×10 -4 Pa, and then introduce Ar gas and adjust the Ar gas flow rate to make the working gas pressure in the chamber 0.4Pa~0.7Pa.
6. The method for magnetron sputtering FeCrAlTi-yttrium oxide coating on the surface of austenitic 316L steel according to claim 5, characterized in that The Ar gas flow rate was adjusted to 90 sccm / min to 120 sccm / min.
7. The method for magnetron sputtering FeCrAlTi-yttrium oxide coating on the surface of austenitic 316L steel according to claim 1, characterized in that The pre-sputtering described in step 1 is specifically performed for 5min to 10min under the conditions of a working pressure of 0.4Pa to 0.7Pa in the chamber, a temperature of 60°C to 150°C in the chamber, a DC current of 0.2A to 0.4A and a negative bias voltage of 300V to 500V in the chamber.
8. The method for magnetron sputtering FeCrAlTi-yttrium oxide coating on the surface of austenitic 316L steel according to claim 1, characterized in that The thickness of the magnetron sputtering coating in step 2 is 5 μm to 7 μm.
9. The method for magnetron sputtering FeCrAlTi-yttrium oxide coating on the surface of austenitic 316L steel according to claim 8, characterized in that In step 2, the magnetron sputtering coating is performed for 2 h to 4 h.
10. The method for magnetron sputtering FeCrAlTi-yttrium oxide coating on the surface of austenitic 316L steel according to claim 1, characterized in that In step 2, adjust the sample stage speed to 10 r / min to 15 r / min.
Citation Information
Patent Citations
Process for applying a high-temperature corrosion protection layer to a component consisting in the base body of a superalloy or of a high-melting metal
CH660200A5
ODS (ozone depleting substance) high temperature alloy added with composite oxide nanoparticles and preparation method thereof
CN103966500A
bar.
DE68901929D1
Process for producing a coating on a refractory structural member
US20020022135A1
Method for the application of coatings of oxide dispersion strengthened metals by laser powder injection
US5449536A